KERJASAMA SISTER CITY BANDUNG - SEOUL PERIODE TAHUN 2016-2020 DI BIDANG E-GOVERNMENT - Ivonne Chandra Dewi, (2022)
This research discusses the cooperation conducted by Bandung, Indonesia - Seoul, Republic of Korea in the scheme of Sister City Cooperation in the Smart City sector. The sister city cooperation between Bandung and Seoul is a cooperation between city government which was intended to strengthening the relationship between both parties who is focused on the smart city development cooperation in Bandung. This study discusses the causes of why the sister city cooperation between Bandung and Seoul in e-government is not running optimally by using explanative qualitative methods and also interview and literature studies research techniques to answer the research question. In analyzing this research, the author also uses theory of international cooperation, paradiplomacy, sister city and smart city. The results of the study explained that this collaboration did not run optimally due to differences in the levels of government of the two cities, the change of mayors, the lack of development funds, and the COVID pandemic that has been going on since 2020.